2022
DOI: 10.3390/diagnostics12071750
|View full text |Cite
|
Sign up to set email alerts
|

MELIF, a Fully Automated Liver Function Score Calculated from Gd-EOB-DTPA-Enhanced MR Images: Diagnostic Performance vs. the MELD Score

Abstract: In the management of patients with chronic liver disease, the assessment of liver function is essential for treatment planning. Gd-EOB-DTPA-enhanced MRI allows for both the acquisition of anatomical information and regional liver function quantification. The objective of this study was to demonstrate and evaluate the diagnostic performance of two fully automatically generated imaging-based liver function scores that take the whole liver into account. T1 images from the native and hepatobiliary phases and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Compared to the classic rrT1, which is based on manual measurements of individual regions of interest, the MELIF score is calculated fully automatically for the entire liver and takes into account several patient-specific factors such as size, weight and liver volume. In the first retrospective study to investigate this matter, the MELIF score was shown to perform better than the whole liver rrT1 score based on the MELD score as a reference for liver function 25 . In this study, the MELIF score correlated strongly with surrogate parameters of liver function, such as the MELD, CP, and ALBI scores, and it demonstrated the strongest correlation with the ALBI score (r = − 0.65).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the classic rrT1, which is based on manual measurements of individual regions of interest, the MELIF score is calculated fully automatically for the entire liver and takes into account several patient-specific factors such as size, weight and liver volume. In the first retrospective study to investigate this matter, the MELIF score was shown to perform better than the whole liver rrT1 score based on the MELD score as a reference for liver function 25 . In this study, the MELIF score correlated strongly with surrogate parameters of liver function, such as the MELD, CP, and ALBI scores, and it demonstrated the strongest correlation with the ALBI score (r = − 0.65).…”
Section: Discussionmentioning
confidence: 99%
“…The MELIF score was calculated fully automatically using prototype software, with Eq. ( 3 ) describing the previously published calculation methodology 25 . The equation contains patient-specific factors (p) such as height, weight and liver volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation